(3cJGH GdMejGJs - (3ESMGb Hf SdjeGf GdGSQGFjdj, CHh jYbhH,J (B320 (3g` s ((3jMi GdeWQR GdOeTbi s)
(3ChdgG (B:s
(3cJGH eLehY ef CbGhjd GdChGFd ai GdMejGJ , eeG Yfi HLeYg hJCdjag GdMcje ESMGb Hf SdjeGf GdESQGFjdi , hgh NeS ebGdGJ s
(3BNQgG (B:s
(3hUGQJ GdMei GdLfHjI UYHI dLOI GdOe GdehdO dgG , hbQHgG ef GdbdH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B77 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2109) s
Keywords: (3GdWHs